Pelatihan Daring Eksplorasi Cerita Bermuatan Karakter Mahasiswa Persiapan Kuliah kerja Nyata - Erni, Sukma; Susiba, Susiba; Syafrida, Syafrida; Sakilah, Sakilah; Hasgimianti, Hasgimianti; Syarifuddin, Syarifuddin; Herlina, Herlina (Lembaga penelitian dan pengabdian kepada masyrakat, 2024)
The training aims to strengthen the skills of students who will take part in the KKN program to the community. Stories are often used as a medium to build closeness with village children where the KKN program is implemented. Therefore, it requires the skill of making impromptu stories that contain social values that want to be instilled in children. Character-laden storytelling skills are expected to be an additional provision to strengthen scientific abilities that are ready to be applied in the field during the KKN period. Attended by 33 students using zoom meeting. Activities are carried out for 3 days with part-time class activities for 2 days. More part-time is carried out independently outside of zoom classes. The method used is participatory action (PAR) using cycles. The results obtained are the product of stories created by participants and increased ability to make impromptu stories.